Kite string injury: a thin line between harmless sport and grievous injury - Gupta, Pradeep; Jain, Ayush; Patil, Aditya Nanasaheb; Thakor, Rushin; Kumar, Sharad (International Journal Of Community Medicine And Public Health, 2018)
Background: Kite flying is a common hobby and sport in many countries. Injuries related to kites are on the rise, but there is a relative paucity of data and literature on this subject. Methods: A retrospective review of all patients who presented with injuries directly related to kite strings was done. All such cases presenting in January 2018 were included. Other indirect or secondary injuries were excluded. Results: A total of 187 patients were identified. Males were most commonly affected. The most common age group affected was 16-20 years and head and neck was most frequently involved. There were no cases of mortality. Conclusions: A seemingly harmless game of kite flying a kite can cause grievous harm - even death - not only to the flyer, but also to innocent others. This study attempts to highlight these dangers and emphasizes that potential threats have to be understood and addressed adequately.